Influence of Early Measures Against COVID-19 on Oral and Maxillofacial Surgery Training in Mongolia (Central Asian Journal of Medical Sciences, 2023)
Objectives: This study aimed to evaluate the experiences of the oral maxillofacial surgery (OMFS) residents who worked as quarantine supervisors and its influence on their training. Methods: An online survey was performed by the Department of Oral and Maxillofacial Surgery, School of Dentistry, Mongolian National University of Medical Sciences. All residents of the first and second years were invited to participate anonymously. The link to the survey was sent via e-mail. Results: The duty and tasks mainly required little medical specialty, yet their knowledge and skill to respond to the medical emergencies were insufficient to supervise quarantined persons. The residents who were mobilized to work at the quarantine places missed certain clinical training opportunities. Conclusion: Due to the measures against the Covid-19 pandemic, the oral and maxillofacial residents lost their opportunity to complete their full required rotations.